FINANCIAL PERFORMANCE AND MARKET VALUE ADDED EFFECT ON STOCK PRICES AT INFRASTRUCTURE, UTILITIES AND TRANSPORTATION COMPANIES REGISTERED IN THE SHARIA SECURITIES LIST FOR THE PERIOD OF 2016-2018 - Riska Alwiyati; Rahma Yudi Astuti (Islamic Business and Management Journal, 2020)
ABSTRACTSharia stocks in Indonesia have increased, by observing its development from sharia capital market statistics. Sharia shares increased by 27%, with a market capitalization value of the Indonesia Stock Exchange (IDX) of Rp 3,666,688.31. The increase of sharia stock is due to the large number of companies that have high share value. One of the companies, is infrastructure, utilities and transportation companies, which contributed to 15.17% in increasing sharia stock. Stock prices is present value of cash flows to be received by shareholders in the future. The purpose of this study is to analyze the effect of financial performance and market value added on stock prices. This type of research is quantitative. The data analysis technique of this study uses panel data regression because it uses cross section and time series data. The sample used in this study selected 19 companies from infrastructure, utilities and transportation companies that were registered in the sharia securities list during the 2016-2018 period. The results of this study showed market value added have no significant positive effect on stock prices. It means that the company did not succeed in increasing the value of capital invested by investors. Otherwise, financial performance has an influence on stock prices with earning per share results have a significant positive effect on stock prices. It means the company's management has succeeded in generating profits for shareholders and earning per share have effect on stock prices.